Linking omics and ecology to dissect interactions between the apple proliferation phytoplasma and its psyllid vector Cacopsylla melanoneura. (December 2020) - Weil, Tobias; Ometto, Lino; Esteve-Codina, Anna; Gómez-Garrido, Jèssica; Oppedisano, Tiziana; Lotti, Cesare; Dabad, Marc; Alioto, Tyler; Vrhovsek, Urska; Hogenhout, Saskia; Anfora, Gianfranco
Abstract: Phytoplasmas are bacterial plant pathogens that are detrimental to many plants and cause devastating effects on crops. They are not viable outside their host plants and depend on specific insect vectors for their transmission. So far, research has largely focused on plant-pathogen interactions, while the complex interactions between phytoplasmas and insect vectors are far less understood. Here, we used next-generation sequencing to investigate how transcriptional profiles of the vector psyllid Cacopsylla melanoneura (Hemiptera, Psyllidae) are altered during infection by the bacterium Candidatus Phytoplasma mali (P. mali), which causes the economically important apple proliferation disease. This first de novo transcriptome assembly of an apple proliferation vector revealed that mainly genes involved in small GTPase mediated signal transduction, nervous system development, adhesion, reproduction, actin-filament based and rhythmic processes are significantly altered upon P. mali infection. Furthermore, the presence of P. mali is accompanied by significant changes in carbohydrate and polyol levels, as revealed by metabolomics analysis. Taken together, our results suggest that infection with P. mali impacts on the insect vector physiology, which in turn likely affects the ability of the vector to transmit phytoplasma. Graphical abstract: Image 1 Highlights: First de novo transcriptome assembly and annotation of an apple proliferation vector. Psyllid gene expression and metabolome are affected by Candidatus P. mali infection. The associated cellular and behavioural processes may enhance pathogen transmission. These findings can assist novel and sustainable pest control strategies.